Three new records of Anthocerotophyta for Western Africa (Sierra Leone) based on spore ornamentation of a specimen collected by A. Harrington, with an emphasis on Anthoceros sect. Fusiformes Grolle. (2nd April 2020) - Sérgio, Cecília; Draper, David; Porley, Ronald D.
ABSTRACT: Introduction. During an investigation into the world-wide distribution of Anthoceros caucasicus Steph., we examined a voucher collected from Sierra Leone by A. J. Harrington in 1966 and subsequently studied by E. W. Jones. Methods. Based on spore observations using light and scanning electron microscopy we found that three Anthocerotophyta taxa were present in this mixed collection. Key results. We report Anthoceros aff. bharadwajii Udar & A.K.Asthana new to Africa, Phaeoceros laevis (L.) Prosk. new to Sierra Leone and tropical Africa, and Anthoceros punctatus L. new to Sierra Leone and western mainland Africa. Conclusions. Anthoceros caucasicus should be removed from the Sierra Leone bryoflora list, and possibly from tropical Africa.